Assessment of service quality in the hotel industry: use of fuzzy hybrid methodologies - Stefano, Nara Medianeira; Zattar, Izabel Cristina; Casarotto Filho, Nelson (Revista de Administração da UFSM, 2020)
Considering that, service quality is an abstract and elusive construct because of three characteristics of services: intangibility, heterogeneity, and inseparability of production and consumption. In that way, we define service quality as perceived by the customer. Thus for service providing organizations the interpretation of customer needs is critical. The good performance in services strengthens competitiveness and establish a relationship with the customer, consolidating the brand, communication with the market. In this context, study aimed to assess the services quality in large hotel located in Santa Catarina – Brazil, with participation of 187 guests. We used the SERVQUAL method to collect data on a questionnaire based dimensions of quality. To calculate the expected weights and perception was used FAHP (Fuzzy Analytic Hierarchy Process). As a result, these aspects are presented where the expectation of the guests regarding the service is greater than that found reality, allowing thus the company strategically align its future investments.